Intelligent Systems for Computer Modelling Proceedings of the 1st European-Middle Asian Conference on Computer Modelling 2015, EMACOM 2015 - Styskala, Vitezslav; Kolosov, Dmitrii; Snasel, Vaclav; Karakeyev, Taalaybek; Abraham, Ajith (Advances in Intelligent Systems and Computing, 2016)
This volume of Advances in Intelligent Systems and Computing contains papers presented at the 1st European-Middle Asian Conference on Computer Modelling, EMACOM 2015. This international conference was conceived as a brand new scientific and social event of mutual collaboration between the VSB - Technical University of Ostrava (Ostrava, Czech Republic) and the Kyrgyz National University named after J. Balasagyn (Bishkek, Kyrgyz Republic). The aim of EMACOM 2015 was to present the latest development in the field of computer-aided modelling as an essential aspect of research and development of innovative systems and their applications. The conference showed that together with simulations, various modeling techniques, enabled and encouraged by the rapid development of high-performance computing platforms, are crucial for cost-efficient design, verification, and prototyping of solutions in many diverse industrial fields spanning the whole range from manufacturing, mining, machinery, and automotive industries to infrastructure planning and development, economics, energy, and modern agriculture and food industry.